2019
DOI: 10.1107/s2414314619000531
|View full text |Cite
|
Sign up to set email alerts
|

6-Bromo-2-(4-chlorophenyl)-3-[(1-octyl-1H-1,2,3-triazol-4-yl)methyl]-3H-imidazo[4,5-b]pyridine

Abstract: In the title compound, C23H26BrClN6, the imidazo[4,5-b]pyridine ring system (r.m.s. deviation = 0.012 Å) is inclined at angles of 19.37 (12) and 89.27 (13)° to the phenyl and triazole rings, respectively, while the phenyl and triazole rings subtend a dihedral angle of 71.23 (15)°. In the crystal, the molecules are linked by C—H...NI and bifurcated C—H...(NT,NT) (I = imidazo[4,5-b]pyridine and T = triazole) hydrogen bonds into a double-column structure propagating along the b-axis direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Starting from preformed bicyclic building blocks 32, Bourichi et al indeed observed alkylation on both N-3 (34) and N-4 (35) atoms (Sch. 6A) [26]. The reaction was performed in DMF under phase transfer catalysis conditions alkylating reagents 33.…”
Section: Sch (5) Synthesis Of the Kinase Inhibitor 31mentioning
confidence: 99%
“…Starting from preformed bicyclic building blocks 32, Bourichi et al indeed observed alkylation on both N-3 (34) and N-4 (35) atoms (Sch. 6A) [26]. The reaction was performed in DMF under phase transfer catalysis conditions alkylating reagents 33.…”
Section: Sch (5) Synthesis Of the Kinase Inhibitor 31mentioning
confidence: 99%
“…Of these, two had a -CH 2 CH 2 X-(X = O, NH) chain connecting a saturated nitrogen atom [corresponding to N2 in (I)] to an ortho position of the phenyl ring and so were considered less comparable to (I) than the remainder, which can be represented by the general structure (III) ( . For R = 4-ClC 6 H 4 and R" = Br there are two reports of the compound with R 0 = 1-octyl-1H-1,2,3-triazol-4-yl)methyl [XITLUK (Bourichi et al, 2019a) and XITLUK01 (Bourichi et al, 2019b)]. The dihedral angle between the plane of the 4dimethylaminophenyl group and the mean plane of the imidazopyridine unit is ca 19 in XITLUK and ca 49 in UCOXES.…”
Section: Database Surveymentioning
confidence: 99%